Measuring covid-19 related health literacy in healthcare professionals—psychometric evaluation of the hl-cov-hp instrument - Hiltrop, Kati; Hiebel, Nina; Geiser, Franziska; Kriegsmann-Rabe, Milena; Gambashidze, Nikoloz; Morawa, Eva; Erim, Yesim; Weidner, Kerstin; Albus, Christian; Ernstmann, Nicole (International Journal of Environmental Research and Public Health, 2021)
Background: Thus far, there is no instrument available measuring COVID-19 related health literacy of healthcare professionals. Therefore, the aim of this study was to develop an instrument assessing COVID-19 related health literacy in healthcare professionals (HL-COV-HP) and evaluate its psychometric properties. Methods: An exploratory factor analysis, a confirmatory factor analysis, and descriptive analyses were conducted using data from n = 965 healthcare professionals. Health literacy related to COVID-19 was measured with 12 items, which were adapted from the validated HLS-EU-Q16 instrument measuring general health literacy. Results: Exploratory factor analysis demonstrated that 12 items loaded on one component. After removing one item due to its high standardized residual covariance, the confirmatory factor analysis of a one-factor model with 11 items showed satisfactory model fit (χ2 = 199.340, df = 41, χ2 /df = 4.862, p < 0.001, RMSEA = 0.063, CFI = 0.963 and TLI = 0.951). The HL-COV-HP instrument showed good internal consistency (Cronbach’s alpha 0.87) and acceptable construct reliability. Conclusions: The HL-COV-HP is a reliable, valid, and feasible instrument to assess the COVID-19 related health literacy in healthcare professionals. It can be used in hospitals or other healt hcare settings to assess the motivation and ability of healthcare professionals to find, understand, evaluate, and use COVID-19 information.
CRIS-Team Scopus Importer:2021-11-19
Keywords: Confirmatory factor analysis; COVID-19; Exploratory factor analysis; Health literacy; Healthcare professionals; SARS-CoV2-pandemic